Linnaemya bergstroemi n. sp. (Diptera: Tachinidae)—a new parasitoid fly from the Finnish Lapland - Pohjoismäki, Jaakko; Haarto, Antti (Zootaxa, 2015)
A new tachinid species, Linnaemya bergstroemi n. sp., is described from the Finnish Lapland. The new species closely resembles the Nearctic species Linnaemya anthracina Thompson, but can be readily distinguished from it by the characters described in this paper. The taxonomic placement of the two species is discussed in the light of morphological and CoI sequence similarities with Linnaemya Robineau-Desvoidy species in the subgenera Ophina Robineau-Desvoidy and Bonellimyia Townsend. Known aspects of the new species’ biology and distribution are reviewed.